Demographic Variables and Web Information Seeking Behavior of Final Year University Students in Nigeria - Oladokun, Bolaji David; Udofot, Columbus (Journal of Information and Knowledge, 2024)
The study examined demographic variables and web information-seeking behaviour of final-year university students in Nigeria. The study utilized a survey research approach, employing a questionnaire as the primary data collection tool. The research population consisted of 377 final-year undergraduates selected purposively from three universities in Nigeria. The results of the study indicated that students primarily sought web-based information to complete class assignments and research projects. Additionally, challenges such as information overload and the high cost of subscriptions were identified in connection with students’ online information-seeking behaviour. The study concluded that a good number of students frequently seek information from Google search and Wikipedia as well as electronic journals, which has helped them meet the demands of their academic pursuits. The study recommended, among others, that university libraries should encourage faculty members to continually assign research tasks to students that will compel them to visit their electronic libraries, where they will get new knowledge and acquire skills in web information searching. Librarians, through user education programmes, should organize practical sessions where students would be taught how to search and retrieve relevant web resources.